Verses on Auschwitz : images of the Holocaust in modern American poetry - Pager, Chet Kelii-Wallraff (Department of English Language and Literature, 2016)
This thesis examines how poetic responses to the Holocaust in America, when they emerged, have differed from the novels addressing the same subject; how the Second World War has challenged, in a way the First World War did not, basic humanistic assumptions regarding the image of man, the role of God, the benefits of civilisation & culture, and the humanising power of art or reason; and how this impact has influenced modern trends in poetry. After an extensive background section documenting the impact the Holocaust and Second World War have made upon the literary imagination, an extensive review is conducted of the varied critical positions and criteria, both aesthetic and ethical, from which American literary responses have been evaluated. Among the major critical positions is the belief that there should be no literary response to the Holocaust; that this literary response must primarily serve to document and testify; that the Holocaust should not be addressed imaginatively by non-victims; and that the Holocaust should not be used as a metaphor to convey some other subject or theme. These and other critical standpoints are discussed in relation to works by ten American poets whose poetry is representative of the ways in which the Holocaust has impacted on the poetic imagination, the breadth of poetic responses to this atrocity, and the range of difficulties and corresponding criticisms which are associated with almost all attempts to respond creatively to the Holocaust. The poets examined are Sylvia Plath, Anne Sexton, Maxine Kumin, Adrienne Rich, Denise Levertov, Stephen Berg, Van Brock, W.D. Snodgrass, William Heyen and Charles Reznikoff. Where illustrative, comparisons to relevant European poets have been made, including Nellie Sachs and Paul Celan. It was concluded that certain poets (Levertov, Rich, Heyen), as well as certain critical standpoints (Ezrahi, Langer, James Young) did more justice to the reality of the Holocaust and the challenges it poses to the literary and poetic imagination. Bibliography: p. 135-140.